Reliability and Validity of the Greek Version of the Oral Mucositis Weekly Questionnaire in the Head and Neck Cancer Context - Thrasyvoulou, Stephanie; Tsitsi, Theologia; Katodritis, Nicos; Vomvas, Dimitrios; Charalambous, Melanie; Charalambous, Andreas (My University, 2021)
Background and Purpose Oral mucositis is one of the most common treatment-induced adverse side effects in head and neck cancer patients. The purpose was to evaluate the reliability and validity of the Greek version of the Oral Mucositis Weekly Questionnaire-Head and Neck Cancer (OMWQ-HN). Methods The data were retrieved from 72 head and neck cancer patients who were undergoing oral radiotherapy as monotherapy or in combination with chemotherapy and surgery. Data analyses included internal consistency reliability, criterion related validity, and cross-sectional validity. Results The OMWQ-HN demonstrated good criterion validity. Strong correlations were observed between OMWQ-HN with EORTC QLQ-C30 and EORTC QLQ-H&N35 that showed good concurrent validity. The tool has a strong internal consistency index with α = .92. Conclusion The Greek version of OMWQ-HN is a reliable and valid instrument that can be used for the assessment of oral mucositis in this context.
Keywords: OMWQ-HN; Cancer patients; Oral mucositis; Reliability; Validation